EUS-guided biliary drainage with a novel electrocautery-enhanced lumen apposing metal stent as first approach for distal malignant biliary obstruction: a prospective study - Mangiavillano, Benedetto; Moon, Jong Ho; Facciorusso, Antonio; Di Matteo, Francesco; Paduano, Danilo; Bulajic, Milutin; Ofosu, Andrew; Auriemma, Francesco; Lamonaca, Laura; Yoo, Hae Won; Rea, Roberta; Massidda, Marco; Repici, Alessandro (Endoscopy International Open, 2022)
Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) represents the gold standard for jaundice palliation in malignant biliary obstruction (MBO) patients. Biliary drainage using electrocautery lumen apposing metal stent (EC-LAMS) is currently a well-established procedure when ERCP fails. We aimed to assess the technical and clinical success of a new EC-LAMS as the first approach to the palliation of malignant jaundice due to MBO in patients unfit for surgery.Patients and methods Twenty-five consecutive patients undergoing endoscopic-guided biliary drainage with the new EC-LAMS were prospectively enrolled. Clinical success was defined as bilirubin level decrease > 15 % 24 hours after EC-LAMS placement.Results Mean age was 76.6 ± 11.56 years, and male patients were 10 (40 %). EC-LAMS placement was technically feasible in 24 patients (96 %) and clinical success rate was 100 %. Only one patient (4 %) experienced a misplacement rescued by an immediate second EC-LAMS placement. The mean duration of hospital stay was 4.66 ± 4.22 days. The median overall survival was 7 months (95 % CI 1–7).Conclusions In this preliminary study, the new EC-LAMS seems to allow a single-step palliative endoscopic therapy in patients affected by jaundice due to MBO, with high technical and clinical success and low adverse events. Further large prospective studies are warranted to validate these results.